Successful treatment of immediate allogeneic myeloablative hematopoietic stem cell transplantation from a HLA‐mismatched sibling donor for active systemic epstein–barr virus‐positive T‐cell lymphoproliferative disease of childhood following primary acute epstein–barr virus infection. Issue 4 (2nd February 2015) - Kakinoki, Yasutaka; Matsuoka, Satomi; Hashiguchi, Junichi; Chiba, Koji; Miyake, Takayoshi
Key Clinical Message A 22‐year‐old female was admitted for sustained high fever and diagnosed with systemic Epstein–Barr virus‐positive T‐cell lymphoproliferative disease. As her clinical course was so aggressive, she immediately underwent allogeneic myeloablative bone marrow transplantation from an HLA‐mismatched sibling donor on hospital day 46. The patient has remained in complete remission for 3 years.